Reconstruction of the hip joint in case of pathological dislocation of the hip in children (Texas Journal of Engineering and Technology, 2022)
Pathological hip dislocation is one of the most severe and frequent complications of acute hematogenous osteomyelitis of the femur, suffered in the first months of a child's life and occupies a significant place in the structure of orthopedic diseases of childhood and adolescence